Modern Tourism : Virtual Tourism Conceptualization - Nadiera Putri Ellyana; Taufik Abdullah (Universitas Pendidikan Indonesia, 2024)
The emergence of the industrial revolution 4.0 has profoundly changed various sectors around the world, especially the tourism industry. This study aims to investigate the changes in the traditional tourism model to a modern form, especially virtual tourism, driven by rapid technological advances. Modern tourism will help the world of tourism better so that it will help the economy both micro and macro to individuals in a narrow way and the country in a large way. Using a qualitative descriptive approach, this study conducted a literature review of relevant journals and articles to analyze the impact of virtual technology on tourism. The research findings reveal that (1) virtual tourism increases accessibility, allowing exploration of destinations without geographical boundaries; (2) virtual reality (VR) and augmented reality (AR) technologies provide immersive and interactive experiences that empower tourist engagement; and (3) ethical and data security challenges must be addressed to ensure the sustainability of virtual tourism. The modern tourism industry is very much needed in accordance with the times so that it helps massively develop the modern economy. This insight highlights the need for the tourism industry to adapt to technological changes and consider the impact of virtual tourism for future development.